2008
DOI: 10.1128/jb.01636-07
|View full text |Cite
|
Sign up to set email alerts
|

Functional Differences between Heme Permeases: Serratia marcescens HemTUV Permease Exhibits a Narrower Substrate Specificity (Restricted to Heme) Than the Escherichia coli DppABCDF Peptide-Heme Permease

Abstract: Serratia marcescens hemTUV genes encoding a potential heme permease were cloned in Escherichia coli recombinant mutant FB827 dppF::Km(pAM 238-hasR). This strain, which expresses HasR, a foreign heme outer membrane receptor, is potentially capable of using heme as an iron source. However, this process is invalidated due to a dppF::Km mutation which inactivates the Dpp heme/peptide permease responsible for heme, dipeptide, and ␦-aminolevulinic (ALA) transport through the E. coli inner membrane. We show here that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The large multifunctional binding proteins (DppA, MppA, NikA, and HbpA) recognize and transport substrates other than heme. The second class of smaller proteins, such as HemTUV from Serratia marcescens, ShuTUV from Shigella dysenteriae, and PhuTUV from Pseudomonas aeruginosa, are involved in high-affinity heme transport (5,16,18). No HemTUV orthologs exist in Neisseria or Haemophilus species, but these bacteria have functional outer membrane heme receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The large multifunctional binding proteins (DppA, MppA, NikA, and HbpA) recognize and transport substrates other than heme. The second class of smaller proteins, such as HemTUV from Serratia marcescens, ShuTUV from Shigella dysenteriae, and PhuTUV from Pseudomonas aeruginosa, are involved in high-affinity heme transport (5,16,18). No HemTUV orthologs exist in Neisseria or Haemophilus species, but these bacteria have functional outer membrane heme receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Such systems have been described in pathogens such as Escherichia coli (Otto et al 2005, Suits et al 2006Suits et al 2009;Hagan and Mobley 2009); Vibrio cholerae (Mey and Payne 2001;Wyckoff et al 2004;Wyckoff et al 2006;Wyckoff et al 2007); Shigella (Mills and Payne 1995;Mills and Payne 1997;Wyckoff et al 2005); Pseudomonas aeruginosa (Vasil and Ochsner 1999;Tong and Guo 2007;Vasil 2007;Yukl et al 2010;Jepkorir et al 2010;Cornelis 2010); Serratia marcescens Izadi-Pruneyre et al 2006;Czjzek et al 2007;Benevides-Matos et al 2008;Letoffe et al 2008;Caillet-Saguy et al 2008); Yersinia pestis (Thompson et al 1999;Rossi et al 2001;Perry et al 2003;Mattle et al 2010) and Legionella pneumophila Pope et al 1996). Heme uptake in Gram-positive bacteria is less well studied.…”
Section: Introductionmentioning
confidence: 95%
“…It has for example been demonstrated that a dipeptide transporter mutant of Helicobacter pylori was not able to utilize dipeptides as well as hexa- and nonapeptides [17] . The heme precursor 5-aminolaevulinic acid is a specific substrate of the dipeptide transporter from E. coli and S. typhimurium [23] , [48] . Moreover, ions such as nickel have been associated with dipeptide transporter systems [49] .…”
Section: Discussionmentioning
confidence: 99%